Role of Men in Birth Preparedness: A Qualitative Study of Women Attending Antenatal Clinics in Migori County, Kenya - Joyce Cheptum; Grace Omoni; Waithira Mirie (Mashhad University of Medical Sciences, 2019)
Background & aim: Male involvement is evidently an effective strategy for enhancing maternal health outcomes. Although childbirth has traditionally targeted women, the key roles of men in decision-making and financial support cannot be ignored. This study aimed to analyze women's perception of men in birth preparedness in Migori County, Kenya. Methods: This qualitative study was conducted on 32 pregnant women attending selected public health facilities in Migori County from January to March, 2016, using conventional content analysis. The study population was selected through purposive sampling technique. Data collection was performed by means of focus group discussions (FGD) organized in four high-volume health facilities. Discussions were recorded based on FGD guidelines. Subsequently, the recorded data were transcribed and reduced into themes. The thematic analysis of the results was reported in the form of narration. Results: The analysis of the data led to the identification of some important themes, including decision making for labor and delivery, financial support, birth companionship, house caretaking in the absence of women, and non-involvement of men in birth preparedness. Conclusion: Men play a key role in birth preparedness in terms of economic and emotional support. Although some cultures prohibit men from participating in the process of birth preparedness, there is a need to educate men in this regard.It is recommended to make more efforts to encourage men's participation through community education, which can effectively modify prohibitive cultural practices.